Analisis Bentuk Interjeksi dan Maknanya Dalam Komik Cedric Karya Raoul Cauvin - Ainnaya Hafifah Ningrum; B. Wahyudi Joko Santoso (STKIP Singkawang, 2025)
This study aims to describe the types and contextual meanings of interjections founded in two French-language comics, Classe Tout Risqué and Au Pieds J’ai Dit by Raoul Cauvin. Comics were selected as the object of study due to their multimodal nature, effectively conveying emotions through the integration of images and language. The research adopts a mixed-methods approach, combining quantitative analysis of interjection frequency and qualitative interpretation through referential analysis. The results identified 54 interjection forms categorized into onomatopoeia, nouns, verbs, adjectives, adverbs, and minor sentences, each expressing various emotional or communicative functions. These findings contribute to linguistic studies in multimodal discourse and offer pedagogical insights for French language education, especially in understanding spontaneous verbal expressions in illustrated literary texts.